How the silica determines properties of filled silicone rubber by the formation of filler networking and bound rubber. (20th October 2021) - Shui, Yue; Huang, Lizhao; Wei, Chengsha; Sun, Guangai; Chen, Jie; Lu, Ai; Sun, Liangwei; Liu, Dong
Abstract: Aiming to unveil the correlation among formula, hierarchical structure, and performance of silica filled silicone rubber foams (SRFs), mechanical and structural investigations are performed on three selected samples. Precipitation (P) and fumed (F) silica filled SRFs with diameters of primary particles around 20 nm (PA), 16 nm (FB), and 14 nm (FC) are used, namely SRPA, SRFB, and SRFC . The hierarchical structures are obtained by contrast variation-small-angle neutron scattering (CV-SANS) with an established three-level unified Guinier-exponential/power-law approach. The sizes of both aggregates ( agg ) and agglomerates ( agl ) levels have the correlation of SRPA > SRFB > SRFC . Mass-fractals d f, agg of SRPA, SRFB, and SRFC are 2.16, 2.16, and 2.54, while d f, agl of the set are 2.90, 2.52, and 2.54, respectively. CV-SANS also indicates that the static thickness of bound rubber ( T S BR ) of SRPA, SRFB, and SRFC decreases from 10.3 nm to 7.5 nm, and then to 6.5 nm. Interestingly, low-field 1 H nuclear magnetic resonance (NMR) indicates that the dynamics thickness of bound rubber ( T N BR ) of the set increases from 3.33 nm to 4.35 nm, and then to 4.41 nm. The discrepancy between T S BR and T N BR is ascribed to the interface interaction. Mechanically, three samples present different behaviors, while SRPA and SRFB have similar extension modules and compressive relaxations. According to a modified constitutive model fitting, and with combining the structural information, the roles of filler-filler and filler-rubber interactions on the reinforcement of SRFs are discussed. Graphical abstract: Image 1